Effect of fenbendazole on cow-calf performance and fecal egg counts - Kuhl, Gerry L.; Ridley, R.; Francis, E.; Riat, L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A field trial was conducted with 80 cow-calf pairs to evaluate the effect of deworming both cows and calves with fenbendazole, on cattle performance and internal parasite burden. Midseason and weaning weights of calves in the fenbendazole-treated group averaged 22.4 and 33.5 lb heavier (P<.04), respectively, than controls. Cow and calf fecal egg counts were low throughout the grazing season and were not materially affected by treatment.
Keywords: Beef; Fenbendazole; Performance; Fecal eggs